Antibacterial activity of Eclipta alba (L.) Hassk - Manoj Kumar Pandey, G.N.Singh, Rajeev Kr Sharma, Sneh Lata (Journal of Applied Pharmaceutical Science)
Eclipta alba (L.) Hassk is small branched annual herbaceous plant with a long history of traditional medicines uses in many countries especially in tropical and subtropical regions. The herb has been known for its curative properties and has been utilized as antimytotoxic, analgesic, antibacterial, antihepatotoxic, antihaemorrhagic, antihyperglycemic, antioxidant, immunomodulatory properties and it is considered as a good rejuvenator too. A wide range of chemical compounds including coumestans, alkaloids, thiopenes, flavonoids, polyacetylenes, triterpenes and their glycosides have been isolated from this species. Extracts and metabolites from this plant have been known to possess pharmacological properties. The present study confirmed the antibacterial potential of aerial parts extracts of Eclipta alba in solvents like acetone, ethanol, methanol, aqueous and hexane against selected gram positive and gram negative bacterial species. The antibacterial studies were done by agar well diffusion methods. The MIC and MBC methods were also used. Hexane extract of showed Eclipta alba high antibacterial activity against S.aureus, B.cereus, E.coli, S.typhi, K.pneumoniae,S.pyogenes and P.aeruginosa. whereas acetone, ethanol, methanol and aqueous extracts showed intermediate activity against S.aureus, B.cereus, E.coli, S.typhi, K.pneumoniae, P.aeruginosa, P.mirabilis and S.pyogenes. The inhibitory activities of all the extracts reported were compared with standard antibiotics (Ciprofloxacin 25 µg/ml). An MIC of 90.0µg/ml shown by E.coli and S.aureus was considered to be the best (below 100µg/ml), an MIC of 125.0µg/ml shown by E.coli, K.pneumoni, P.mirabilis and S.typhi was considered to be better (100-500µg/ml) as such by the action of acetone, ethanol, methanol and hexane extracts on test bacterial spp respectively MIC between (500-1000µg/ml) was considered to be good. The aqueous extracts of Eclipta alba showed good activity against S.pyogenes, B.cereus, E.coli and P.aeruginosa. If the dilution was above 1000µg/ml the extract were considered inactive against S.aureus, K.pneumoniae, P.mirabilis and S.typhi. MBC results were similar to MIC results but in the case of MBC the confirmation was made by absence of growth in culture plates after 24 hrs of incubation at 37ºC. A potent antibacterial and hepatoprotective drug could probably be formulated from the plant extract of Eclipta alba to combat the effects of bacterial and hepatotoxic infections.
Keywords: Salvia officinalis, anti-inflammatory, fractionated extracts, peritonitis.